The George W. Bush Defense Program : Policy, Strategy & War - Cimbala, Stephen J. (Book collections on Project MUSE., 2010)
In this insightful series of essays edited by Stephen Cimbala, eleven academic experts prominent in the defense and security think-tank communities assess Bush's defense program. Many also have past or current experience in the U.S. government or the American armed forces. They examine Bush's defense policy and strategy across several critical issues, including Iraq, Afghanistan, terrorism, nuclear arms control, and foreign military sales. In addition, special chapters are devoted to the leadership style of former defense secretary Donald Rumsfeld, to the idea of "victory" as it might apply to Bush's defense decisions, and to the best exit strategy from Iraq for the United States. The lessons learned from the successes and failures in Bush's defense policy, which are clearly presented in The George W. Bush Defense Program, can also be applied to the appraisal of all presidents. --Book Jacket